Organizing women : gender equality policies in French and British trade unions - Guillaume, Cécile (Understanding work and employment relations, 2022)
This book explores the representation of women's interests in the world of work across four trade unions in France and the UK. Drawing on case studies, it unveils the social, organisational and political conditions that contribute to the reproduction of gender inequalities or, on the contrary, allow the promotion of equality.--